2015
DOI: 10.3892/ol.2015.3818
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic features and treatment of breast metastasis from nasopharyngeal carcinoma: A report of two cases and literature review

Abstract: Abstract. Breast metastasis is a rare pattern of distant metastasis from nasopharyngeal carcinoma (NPC) following curative treatment. The present study reported two patients with breast metastasis from NPC and reviewed four such patients reported in the literature, including the analysis of clinical profiles, pathological diagnoses, treatment strategies and outcomes. The breast is a potential metastatic site for patients with NPC following curative treatment; however, thus far, only metachronous breast metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…However, we believe that the clinical history, histopathological findings, and IHC profile clearly confirm the diagnosis of NPC metastatic to the breast in our patient. The ideal treatment for metastatic NPC is chemotherapy and radiotherapy, and patients with solitary breast metastasis from NPC may gain long term survival, as observed by Xiao et al 3 In conclusion, this case highlights the rarity of the NPC lesion and importance of clinical, histopathological, and IHC examination, along with the patients' history, for appropriate diagnosis and treatment.…”
Section: Open Accesssupporting
confidence: 53%
See 3 more Smart Citations
“…However, we believe that the clinical history, histopathological findings, and IHC profile clearly confirm the diagnosis of NPC metastatic to the breast in our patient. The ideal treatment for metastatic NPC is chemotherapy and radiotherapy, and patients with solitary breast metastasis from NPC may gain long term survival, as observed by Xiao et al 3 In conclusion, this case highlights the rarity of the NPC lesion and importance of clinical, histopathological, and IHC examination, along with the patients' history, for appropriate diagnosis and treatment.…”
Section: Open Accesssupporting
confidence: 53%
“…It has been observed that a metastatic breast tumor could occur immediately after the first course of treatment or within 24 months of treatment completion. 1,3 In our case, the patient developed breast metastasis after 21 months of initial treatment for NPC. A comparison of the present case report with previous cases of NPC metastasizing to the breast is summarized in Table 1.…”
Section: Open Accessmentioning
confidence: 62%
See 2 more Smart Citations
“…A previous study has suggested that future perspectives for clinical research should include prospective and observational cohort studies, which may assess the effects of different risk factors in the development of NPC and the effectiveness of investigational treatments (5). Although previous studies have investigated numerous anticancer drugs including nimotuzumab, oxaliplatin and gemcitabine for the treatment of NPC (6)(7)(8)(9), the therapeutic outcomes are not encouraging so far. Therefore, exploring efficient anticancer agents and the potential underlying molecular mechanisms of cellular migration and metastasis in NPC are required.…”
Section: Introductionmentioning
confidence: 99%